DEPRESSION AND SUICIDAL IDEATION AND MODERATING EFFECT OF SUICIDE RESILIENCE AMONG IN-SCHOOL ADOLESCENTS IN IBADAN SOUTH EAST AND OLUYOLE LOCAL GOVERNMENT AREAS OF OYO STATE (2021)
Adolescents have one of the highest rates of suicidal behaviours found in research. Hence, health research and interventions have become a key preference among them. This study therefore, examined Depression And Suicidal Ideation And Moderating Effect of Suicide Resilience Among In-School Adolescents In Ibadan South East And Oluyole Local areas of Oyo state. The descriptive survey design was used for the study and a combination of random and purposive sampling techniques were employed to select 275 participants with age ranges between 15 and 19years, x =16.87, SD=1.02 into this study. A structured questionnaire focusing on socio-demographic profile, Depression, Suicide Resilience and Suicidal Ideation was administered to the participants. Five hypotheses were formulated, tested and all were confirmed. Data were analyzed using descriptive statistics, simple regression and independent sample for ttest, point-biserial correlation, biserial correlation multiple regression and hierarchical regression analysis. The results showed that Depression (R2= 0.061, F = 17.753, p<.01) significantly predicted suicidal ideation and behaviour, while gender had significant influence on suicide behavior (t (273) = -4.597, p<.01) among in-school adolescents. In addition t-test, point-biserial correlation results showed gender (rpb= .265, n=273, p= .01). accounted for 7% variance observed in the reported Suicidal behavior among in-school Adolescent. Age also had significant influence on suicide behavior (t (273) = -3.300, p<.01) among in-school adolescents. In addition t-test, biserial correlation results showed Age (rpb= -.175, n=273, p= .05). accounted for 3% variance observed in the reported Suicidal behavior among in-school Adolescent. Additionally, Suicide Resilience and Depression [F(2,272)= 11.74, R=.14, R2 =.02,p<.01] jointly predicted Suicide behavior (ΔR2 =0 .81, p < .001). Meanwhile, the effect of depression on suicidal ideation and behavior was moderated by the interaction between depression and suicide resilience (b = -.285, p < .05) Suicide Resilience can reduce the impact of Depression on suicidal Ideation and Behavior. It suggests that when suicide resilience was high, the association between depression and suicide behavior was the weakest; when suicide resilience was low, the association was the strongest. Additional clinical implications, limitations of the study, and suggestions for future research are addressed.